A problemática do silêncio nas sessões psicanalíticas on-line - Negreiros, Jefferson da Silva (2024)
The present research aimed to comprehend the different types of silence in online psychoanalytic therapy, their various interpretations, and how some professionals respond. This study adopted empirical or field research with a qualitative approach in which questionnaires were applied through Google Forms following specific criteria. Psychologists with training in Winnicottian psychoanalysis and at least five years of clinical experience, who had conducted analyses in both online and face-to-face modalities, were selected. The professionals were chosen through searches on social networks and websites and the IBPW (Instituto Brasileiro de Psicanálise Winnicottiana) affiliated sector. Seventy invitations were sent, and twenty responded, subsequently classified in order of responses. The questionnaires, containing twenty-nine questions (open and closed questions), addressed the theme of silence in the online environment and how it is interpreted and managed in their professional experiences. The research aimed to investigate through empirical observations, possible interpretations and clinical approaches to silence in the online environment, analyzing discourses of Winnicottian psychoanalysts and describing different interpretations and approaches to silence in this type of therapy. The research obtained approval from the ethics committee under the number CAAE: 70976723.3.0000.5482 as an ethical requirement. The results were organized into seven categories of silences and five types of clinical management in online practice. In the final considerations, emphasis was placed on how the analyst deals with silent sessions, being more economical in interpretations due to potential resistances, acting out, a form of psychic refuge, or even a repetition of childhood behavior. However, silence is evaluated as a positive contribution in clinical practice, representing being alone in the analyst's presence as a defensive mental process, as the analysand may interpret the environment as persecutory